Customer Loyalty Behaviour Brand Air Conditioner XYZ: Combination of Expectation- Confirmation Theory, Satisfaction – Loyalty, and Brand Reputation - Edi Supriyono; Ervina Ahyudanari (Institut Teknologi Sepuluh Nopember, 2020)
List of Selected Providers (LSP) is a list stating that goods/ service providers have passed the qualification assessment mechanism at PT XYZ. The qualification assessment process is an important stage in the process of goods/ service procurement because it affects the success of a project. Up to now, the qualification assessment process at PT XYZ has not been managed comprehensively, resulting in delays or failure of project completion. Therefore, to get a qualified and best provider of goods/ services, the qualification assessment process using the Analytic Network Process (ANP) is necessary to be carried out. The process of this research started from selecting criteria through the Delphi method, then performing a pairwise comparison using questionnaires on each of the criteria identified. Subsequently, the data were processed using the ANP software, namely Super Decisions Version 3.2.0 to obtain the weight of each criterion. The next stage was to carry out an assessment of the goods or service providers following the LSP process. The final result of this research was to obtain the weight of each qualification criterion to determine a competent and threshold-passing provider projected to be included in the LSP.